FAKTOR PEMBEDA DALAM KOMUNIKASI LINTAS BUDAYA ANTARA WISATAWAN ASING DENGAN MASYARAKAT LOKAL DI DESA WISATA KANDRI GUNUNGPATI KOTA SEMARANG - Nurul Khotimah (An-Nida : Jurnal Komunikasi Islam, 2019)
Cultural diversity is a necessity in the human community in the world. Cultures have different value systems, so they determine different life goals, and determine ways of communicating that are strongly influenced by language, rules and norms in each culture. So that every communication activity with other people always contains the potential for cross-cultural or intercultural communication, because it will always be in a "culture" that is different from other people. This study aims to find out how cultural differences between foreign tourists and local communities are examined based on the study of cross-cultural communication, so that they can be understood together and avoid culture shock. This research was conducted in the tourist village of Kandri, Gunungpati sub-district, Semarang city with the object of research of foreign tourists who came in the tourist village. The research method used is a qualitative field reserach. Data collection techniques in this study were interviews and observations. The results of the study show that the distinguishing factors in communication can be seen from the verbal and nonverbal language systems, economic systems, educational systems, cultures (values and norms), and religious systems.